Analysis of Legal Institutions, Conflict and Trade - Oloufade, Djoulassi Kokou (Université d'Ottawa / University of Ottawa, 2012)
In the first paper, the effects of trade openness and conflict risk on income inequality are investigated. I obtain that the effect of trade openness on inequality depends on the level of conflict risk. More precisely, there exists a threshold effect: trade openness worsens income inequality in countries where the risk of internal and external conflicts is high. Moreover, I find that countries with higher risk of conflicts are more unequal, and that more ethnically diverse countries increase income inequality. Finally, I obtain that democratic regimes decrease inequality. In the second paper, we analyze the general-equilibrium consequences of property right enforcement in the natural resource sector. Assuming that exclusion requires both private and public enforcement efforts, we compare states that differ by their ability to provide protection services. This ability is referred to as state capacity. We obtain that public protection services can effectively act as either substitutes or complements to private enforcement, and this strongly depends on state capacity. Under low state capacity, an increase in state protection services leads to a drop in national income as labor is drawn away from the directly productive activities. The opposite holds for high-capacity states. As a result, public protection services have an ambiguous effect on national income even though they can unambiguously increase resource rents. In the third paper, we argue that the right to hold dual citizenship can generate important social and economic benefits beyond its political dimension. We assemble a large panel dataset on dual citizenship. We find that in developing countries, dual citizenship recognition increases remittance inflows by US$1.19 billion, GDP and household consumption, and improves child survival. In developed countries, however, dual citizenship recognition decreases remittance inflows by US$1.44 billion, but increases FDI by US$828 billion, raises household consumption, gross capital formation and trade, and provides incentives for skilled workers to move to other countries.
Keywords: Institutions; Property Right Enforcement; Trade Openness; Conflict Risk; Income Inequality; Developing Countries; Developed Countries; State Capacity; Natural Resources; Threshold Effect; Dual Citizenship Legislation; Foreign Direct Investments; Workers' Remittances; Child Mortality and Poverty Alleviation; Household Consumption Expenditures; Migration and Brain Drain; Low and High Skilled Workers